Moderating effect of environmental education in relationship between attitude, perceived behavioural control and subjective norm with waste segregation-at- source behaviour in Putrajaya, Malaysia - Wah, Cheng Kai (2017)
Fast population growth, rapid changing lifestyle, great urbanisation along with aggressive economic development and the rapid changes in consumption rate have accelerated the daily generation and volume rate of municipal solid wastes. Efficient solid waste management has become one of the daunting national challenges, typically in the developing countries, including Malaysia, in order to cope with the solutions for many serious environmental problems. The main purpose of this research was to explore the current scenarios of waste segregation-at-source behaviour in Putrajaya; to evaluate the levels of attitude, perceived behavioural control and subjective norm with waste segregation-atsource behaviour; to investigate the relationship between households’ attitude, perceived behavioural control and subjective norm with waste segregation-atsource behaviour; and to examine the moderating effect of environmental education in relationship between households’ attitude, perceived behavioural control and subjective norm with waste segregation-at-source behaviour. The subject of this research is households who are living in Putrajaya and the sample was selected via multistage sampling method and systematic sampling method. It is a quantitative research by distributing self-administrative questionnaire. The measurements were adapted from different sources to examine participants’ attitude, perceived behavioural control, subjective norm and environmental education with waste segregation-at-source behaviour. The results reveal that attitude (B = 0.005, p = 0.783), perceived behavioural control (B = 0.121, p = 0.000) and subjective norm (B = 0.003, p = 0.907) have positive relationship with waste segregation-at-source behaviour. Besides that, environmental education does moderate relationship between perceived behavioural control (B = -0.010, p = 0.026) but does not moderate relationship between attitude (B = 0.003, p > 0.05) and subjective norm (B = 0.005, p > 0.05) with waste segregation-at-source behaviour positively. The findings provide an insight particularly for the individual, government, educator and non-governmental organisations in Malaysia on factors that they should consider in developing pro-environmental policies. Furthermore, future research recommended to increase the area coverage of research location in a bid to obtain a more reliable data and provide greater generalisation.